The Effect Of Employee Engagement And Work Flexibility On Employee Performance In Manufacturing Companies - Citra, Dela Yulia; Ningrum, Ika Putri Aisya (Lentera Ilmu Nusantara, 2024)
This study aims to analyze the influence of employee involvement and work flexibility on employee performance in the EJIP Cikarang manufacturing industrial area. Using a quantitative approach, the study involved a number of respondents from various departments with a purposive sampling method. Data was collected through questionnaires and analyzed using Structural Equation Modeling with SmartPLS software. The research variables include employee engagement and work flexibility as independent variables, as well as employee performance as dependent variables. The results of the study show that employee engagement and work flexibility have a significant influence on employee performance. Respondents were dominated by women of early productive age with a majority secondary education background. The findings of the study indicate that manufacturing companies can improve employee performance through policies that support engagement and work flexibility. This research makes a theoretical and practical contribution in understanding the dynamics of human resources in the manufacturing sector.